The UCUAAAC promoter motif is not required for high-frequency leader recombination in bovine coronavirus defective interfering RNA. - Chang, R Y (1996)
The 65-nucleotide leader on the cloned bovine coronavirus defective interfering (DI) RNA, when marked by mutations, has been shown to rapidly convert to the wild-type leader of the helper virus following DI RNA transfection into helper virus-infected cells. A model of leader-primed transcription in which free leader supplied in trans by the helper virus interacts by way of its flanking 5'UCUAAAC3' sequence element with the 3'-proximal 3'AGAUUUG5' promoter on the DI RNA minus strand to prime RNA replication has been used to explain this phenomenon. To test this model, the UCUAAAC element which occurs only once in the BCV 5' untranslated region was either deleted or completely substituted in input DI RNA template, and evidence of leader conversion was sought. In both cases, leader conversion occurred rapidly, indicating that this element is not required on input RNA for the conversion event. Substitution mutations mapped the crossover region to a 24-nucleotide segment that begins within the UCUAAAC sequence and extends downstream. Although structure probing of the bovine coronavirus 5' untranslated region indicated that the UCUAAAC element is in the loop of a prominent stem and thus theoretically available for base pair-directed priming, no evidence of an unattached leader early in infection that might have served as a primer for transcription was found by RNase protection studies. These results together suggest that leader conversion on the DI RNA 5' terminus is not guided by the UCUAAAC element and might arise instead from a high-frequency, region-specific, homologous recombination event perhaps during minus-strand synthesis rather than by leader priming during plus-strand synthesis.